Color imaging and characterization of aerosol particles with digital holography - Giri, Ramesh (Kansas State University, 2022)
Aerosols are everywhere in the atmosphere. Therefore, it is critical to investigate their morphology in situ to understand how aerosols influence the environment and human health. In addition, the characterization of aerosols requires a fundamental understanding of properties such as shape, size, and color. One of the promising methods for characterizing aerosol particles is light scattering. Digital holography, also based on particle light scattering phenomena, works best for studying particle morphology in situ, which often addresses the inverse problem. This work describes an experimental approach to imaging freely flowing aerosol particles using multiple wave-length digital holography (MWDH). In contrast to conventional methods in DH, this work uses three different wavelength lasers (Red, Green, and Blue) combine to produce an almost white beam. In addition, the method involves a Michelson interferometer to produce holograms. When the backscattered light from the particles coherently mixes with the reference beam, interference patterns (holograms) are created. Using a three-CMOS prism sensor, we record three separate backscattered holograms, one for each wavelength, simultaneously and resolve them without spectral cross-talk. Fresnel diffraction theory is used to reconstruct holograms, which renders a monochrome image for each wavelength. The individual images are combined using the additive color mixing method, with red, green, and blue as primary colors. For size and color balance calibration, various colored micro-spheres (white, red, green, and cyan) are aerosolized, and the holograms are recorded. In addition, various mineral powders of different colors are used to demonstrate the viability of the experiment and the effect of basic speckle noise reduction and white balance approaches. Finally, chromaticity analysis is performed on the color image to illustrate the ability of the MWDH approach to objectively characterize aerosol particles of various shapes, sizes, and colors. Although MWDH has been used in several scientific fields, our study is the first to apply it to objects of micrometer-size scale to study freely flowing coarse-mode particles. This research is also the first to create an MWDH image analysis that allows quantitative characterization of colored particles. The analysis quantifies the color content in the image regardless of the apparent brightness of the color in the image.
Keywords: Aerosol; Digital holography; Light scattering; Chromaticity